ANXIETY OVER TOEFL LISTENING COMPREHENSION AMONG EIGHT-SEMESTER STUDENTS - Sarair, Sarair (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
This study was done to find out how anxious students were about the listening comprehension section of the TOEFL test. Since the TOEFL test's component on listening comprehension is frequently regarded as the most challenging, Lack of understanding could result in anxiety, which would lead to poor language skills and a poor grade. Students from the Islamic faculty at Muhammadiyah Aceh University who are eight-semester students participated in this study by taking the TOEFL exam at the university's language center using a random sample methodology. This study employs the descriptive method and is qualitative in nature. Both an interview and a questionnaire were used to gather the data. According to the survey's findings, the majority of students experience anxiety before taking the TOEFL's listening comprehension section. They become anxious and perplexed when they do not comprehend every word in the TOEFL listening comprehension portion because they do not understand the pronunciation of a native speaker who is not like them. They also become anxious when they cannot tie a topic or term to their prior knowledge. The interview led the author to the conclusion that students' challenges on the Listening Comprehension section of the TOEFL are due to their lack of preparation.